2013
DOI: 10.4314/ajtcam.v11i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, phytochemical analysis and antioxidant activity of crude extracts from Rhizomes of <i>Elephantorrhiza Elephantina</i> and <i>Pentanisia Prunelloides</i>

Abstract: Background: Elephantorrhiza elephantina (Ee) and Pentanisia prunelloides (Pp) are two medicinal plants which are widely used to remedy various ailments including diarrhoea, dysentery, inflammation, fever, rheumatism, heartburn, tuberculosis, haemorrhoids, skin diseases, perforated peptic ulcers and sore joints in southern Africa (South Africa, Swaziland, Botswana and Zimbabwe). The following study was conducted to explore the in vitro cytotoxicity, antioxidant properties and phytochemical profile of the two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…Recently, Msimanga et al [55] isolated the following compounds from hexane root extracts of E. elephantina : hexadecanoic 15 , 9,12-octadecadienoic 16 , 9-octadecenoic 17 , octadecanoic acid 18 , butanedioic acid 19 , benzoic acid 20 , 3-phenyl-2-propenoic acid 21 , nonanedioic acid 22 , tridecanoic acid 23 , methyl pentadecanoate 24 , methyl hexadec-9-enoate 25 , methyl hexadecanoate 26 , methyl 3-(3,5-di-tert-butyl-4-hydroxy-phenyl)propionate 27 , cis-10-Heptadecenoic acid 28 , methyl heptadecanoate 29 , methyl octadecanoate 30 , cis-5,8,11,14,17-eicosapenta-enoic acid 31 , eicosanoic acid 32 , methyl tetracosanoate 33 , pentacosanoic acid 34 , hexacosanoic acid 35 , methyl octacosanoate 36, and tetradecanedioic acid 37 . The phytochemical studies of the rhizome extracts of E. elephantina carried out by Mpofu et al [54] showed the presence of anthraquinone 38 , triterpenoids oleanolic acid 39 , diosgenin 40 , rhamnose 41 , glucuronic acid 42, and arabinose 43 . In another phytochemical evaluation of E. elephantina rhizome extracts, Mpofu et al [56] isolated kaempferol 2 , epicatechin 14 , glucuronic acid 42 , arabinose 43 , epigallocatechin gallate 44 , quercetin 45, and epicatechin gallate 46 .…”
Section: Phytochemistrymentioning
confidence: 99%
“…Recently, Msimanga et al [55] isolated the following compounds from hexane root extracts of E. elephantina : hexadecanoic 15 , 9,12-octadecadienoic 16 , 9-octadecenoic 17 , octadecanoic acid 18 , butanedioic acid 19 , benzoic acid 20 , 3-phenyl-2-propenoic acid 21 , nonanedioic acid 22 , tridecanoic acid 23 , methyl pentadecanoate 24 , methyl hexadec-9-enoate 25 , methyl hexadecanoate 26 , methyl 3-(3,5-di-tert-butyl-4-hydroxy-phenyl)propionate 27 , cis-10-Heptadecenoic acid 28 , methyl heptadecanoate 29 , methyl octadecanoate 30 , cis-5,8,11,14,17-eicosapenta-enoic acid 31 , eicosanoic acid 32 , methyl tetracosanoate 33 , pentacosanoic acid 34 , hexacosanoic acid 35 , methyl octacosanoate 36, and tetradecanedioic acid 37 . The phytochemical studies of the rhizome extracts of E. elephantina carried out by Mpofu et al [54] showed the presence of anthraquinone 38 , triterpenoids oleanolic acid 39 , diosgenin 40 , rhamnose 41 , glucuronic acid 42, and arabinose 43 . In another phytochemical evaluation of E. elephantina rhizome extracts, Mpofu et al [56] isolated kaempferol 2 , epicatechin 14 , glucuronic acid 42 , arabinose 43 , epigallocatechin gallate 44 , quercetin 45, and epicatechin gallate 46 .…”
Section: Phytochemistrymentioning
confidence: 99%
“…The results show that most abundant compounds found in the leaf and rhizome of P. prunelloides were flavonoids, alkaloids and saponins. The high concentration of flavonoids in P. prunelloides can be suggested to be responsible for its antioxidant reported activities (Mpofu et al, 2014). The leaves had lower concentrations of these secondary metabolites than the rhizomes.…”
Section: Quantitative Phytochemical Screeningmentioning
confidence: 99%
“…Phytochemical screening of P. prunelloides indicate high concentration of alcohol precipitable solids (0.7-7.0%) and amino acids, while sucrose and (−)-epicatechin have been isolated (Ndlovu, 2007). Palmitic acid was identified as a major compound in P. Prunelloides (Yff et al, 2002), diosgenin and oleanolic acid have also been isolated from the rhizome extract of P. prunelloides (Mpofu et al, 2014). Cytotoxicity and anti-inflammatory activities of P. prunelloides extract has been ascribed to the presence of flavonoids and saponins (Mpofu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 It is also utilize as fodder for animals in South Africa and have been considered as a veterinary medicine. 68,69 A wide range of phytochemicals such as anthocyanidins, 70 anthraquinones, 70 esters, fatty acids, phenolic compounds, flavonoids, 70 glycosides, polysterols, saponins, 71 sugars, tannins, and triterpenoids have been isolated from rhizome extracts of E. elephantina. 72 In some studies aqueous root extracts have been found to exert antimicrobial, antidiarrheal, cytotoxic and anti-inflammatory effects.…”
Section: Elephantorrhiza Elephantinamentioning
confidence: 99%